Fabrication of slag particle three-dimensional electrode system for methylene blue degradation: Characterization, performance and mechanism study. (December 2018) - Liu, Shuan; Wang, Zhaoyang; Li, Junfeng; Zhao, Chun; He, Xinlin; Yang, Guang
Abstract: In order to solve the problem of slag recycling and dyeing wastewater treatment synchronously, the slag particles is used as raw material to prepare the particle electrodes, and the optimum preparation conditions of the slag particle electrodes is obtained through orthogonal test. Scanning electron microscopy, X-ray diffractometer and micro-hole physics and chemical adsorption analyzer are used to characterize and analyze the surface morphology, crystal structure, specific surface area and pore shape of the particle electrode. The operating parameters of the reaction system are optimized, and the energy consumption per order is calculated in optimized experimental conditions. The radical scavenging mechanism of three free radical scavengers (methanol, tert-butanol, and phenol) is studied, and the type of the main active substance participating in degradation of Methylene blue and the location of the degradation reaction are determined. It is speculated that the degradation reaction of Methylene blue occurs in the boundary layer on the external surface of the particle electrodes, not in the aqueous solution. Highlights: Particle electrodes were developed from thermal power plant incineration slag. The particles could strongly improve the efficiency of dyestuff degradation. The reaction position was ascertained via a free radical inhibition experiment.